Higher BMI in heart failure patients is associated with longer survival only in the absence of diabetes
Aims Obesity and diabetes are associated with an increased cardiovascular risk and mortality. Paradoxically, higher BMI is associated with longer survival in heart failure patients. The association between BMI and risk of death in heart failure patients depends on diabetes history. Methods We conducted a retrospective cohort study on 503 ambulatory systolic heart failure patients attending a heart failure clinic, based on abstraction of data from clinical records. Patients were compared according to diabetes history. BMI was analyzed as a continuous variable and dichotomized using 25 kg/m2 as cut-off. Patients’ follow-up was censored at 5 years and all-cause death was the endpoint under study. Results The median age was 69 years and 68% were men; 184 (36.6%) patients had diabetes upon referral. During follow-up, 95 nondiabetic and 69 diabetic patients died. Higher BMI was associated with longer survival in the whole sample, but this association was only reproduced in the subgroup of patients without diabetes [hazard ratio = 0.93; 95% confidence interval (CI): 0.89–0.98 per kg/m2 vs. hazard ratio = 0.99; 95% CI: 0.94–1.04 in diabetic patients; P for interaction = 0.009]. BMI below 25 kg/m2 increased the risk of death by 1.90-fold (95% CI: 1.23–2.94) with a null association in diabetic patients (P for interaction = 0.012). The association between BMI and mortality in nondiabetic heart failure patients was independent of other predictors of prognosis. Conclusion The reported obesity paradox in heart failure can only be observed in nondiabetic patients.